Efeito agudo da suplementação de cafeína e capsaicina no desempenho físico e variáveis fisiológicas de jogadores de futebol - Rafael de Oliveira Ildefonso (2021)
Football is the most popular sport in the world where performance depends on physical, technical, tactical and psychological factors. Ergogenic resources are ways to improve physical work capacity, physiological functions and/or recovery. Caffeine and capsaicin can be ergogenic and ergolytic substances, depending on individual responses, magnitudes of effects and tolerance of one or the other substance. The aim of the study was to verify and compare the acute effect of caffeine and capsaicin ingestion on the performance of soccer players. The sample consisted of 12 soccer players, category under-20 with a mean age of 19.2 ± 0.7 years, mean weight 69.67 ± 7.66 kg and mean height of 175 ± 3 cm, belonging to a professional team. The study was a double-blind, crossover, balanced, placebo-controlled study. Subjects were firstly submitted to three physical test sessions separated by 7 days between each session. Five days after the last session of physical tests, three sessions of an 11 vs.11 game were performed, also with a seven day interval between each session. So the study had a total duration of six weeks. One hour before each session, the athletes ingested a capsule containing placebo, caffeine (6 mg/kg) or capsaicin (12 mg), and immediately before starting the 11 vs. 11, a dose of capsaicin (12 mg) was added. . Physical tests were: countermovement jump test (CMJ), repeated sprints test (RST) and intermittent yo-yo recovery test level 1 (YOYO LV1) The 11 vs. 11 games were performed on a natural grass field with 11 players for each side, in two periods of 45 minutes, with a 15-minute break. The total distance covered (TD), the distance at high intensity (DHI), the counting of accelerations and braking, the distance covered per minute, the sprints, the physical efficiency index (PEI) and the heart rate were monitored through the global positioning system (GPS) with frequency meter attached. The subjective classification of physical status and training intensity and blood lactate were also collected. The results of the present study did not find a statistically significant difference (p>0.05) in the SCM and YOYO LV1 test variables. In the TSR, performance was better only in the worst shot of the caffeine situation when compared to the placebo situation. In 11 vs. 11, no statistically significant difference was found for any of the physical and psychophysiological variables investigated, except for the post-11 blood lactate concentration 11 vs.11, which, in the capsaicin condition, was statistically significantly lower when compared to the caffeine condition. Therefore, at the dosages used, acute caffeine and capsaicin supplementation did not increase the performance of soccer players.